Tinjauan Konseptual Integratif Ontologi Pembelajaran Federasi: Rekonseptualisasi Model Global sebagai Kecerdasan Terdistribusi - Adnan Zulkarnain; Syaad Patmanthara (LPPM STIKI MALANG, 2025)
Federated Learning (FL) is widely recognized as a privacy-preserving architecture, yet the ontological status of the